Study and optimization of alternative MBE‐deposited metallic precursors for highly efficient kesterite CZTSe:Ge solar cells. (19th June 2019) - Giraldo, Sergio; Kim, Shinho; Andrade‐Arvizu, Jacob Antonio; Alcobé, Xavier; Malerba, Claudia; Valentini, Matteo; Tampo, Hitoshi; Shibata, Hajime; Izquierdo‐Roca, Victor; Pérez‐Rodríguez, Alejandro; Saucedo, Edgardo
Abstract: Nowadays, most of the best efficiencies of Cu2 ZnSn(S, Se)4 (CZTSSe) solar cells are obtained from absorber layers fabricated using sequential processes, including the deposition of metallic stack precursors, typically by sputtering, and followed by reactive annealing under chalcogen atmosphere. The sputtering technique is widely known for the easy growth of metallic layers, although the deposition rates, growth morphology and nucleation, or the roughness can sometimes be an issue leading to inhomogeneities in the final layers. Nevertheless, MBE (molecular beam epitaxy) technique could have some advantages to obtain high‐quality metallic layers, with accurate control of the growth due to ultra‐high vacuum conditions and high purity. In this work, we study the use of advanced MBE systems to grow metallic stack precursors, alternatively to sputtering or thermal evaporation techniques, to obtain high‐quality CZTSe:Ge absorbers. Due to differences in the nature of each type of precursor, thermal annealing optimizations are presented by modifying some critical selenization parameters, such as the temperature or the selenium amount in order to obtain well‐crystallized absorbers. Detailed morphological, compositional, and structural characterizations show relevant features of each precursor, mainly related to the formation of MoSe2 at the back interface, and Se and Sn composition after selenization in different conditions. Regarding the solar cell devices, main efficiency limitations come from VOC and FF, which could be tentatively related to a noncontrolled selenization; different precursor reactivity, porosity, or composition; and different alkali diffusion during the reactive annealing. Finally, in the first optimization, a 9.2% efficiency device has been achieved with promising perspectives for future improvements. Abstract : Molecular beam epitaxy (MBE) deposition technique has been studied as a relevant alternative for the fabrication of high efficiency kesterite CZTSe:Ge solar cells, achieving a 9.2% efficiency device (total area). A detailed comparison of sputtered and MBE‐deposited metallic precursors is presented, including morphological, compositional, and structural characterizations of absorbers synthesized using different annealing conditions. Additionally, the photovoltaic parameters of the corresponding solar cell devices are analyzed, elucidating some of the main limitations of this approach.